Surgical correction of class II skeletal malocclusion in an adult patient - Ramakrishnan Balachander; Kandapalanivel Karthik; Anilkumar Katta; Kandasamy Rajasigamani (Wolters Kluwer Medknow Publications, 2014)
Correction of skeletal deformities in adult patients with orthodontics is limited. Orthognathic surgery is the best option for cases when camouflage treatment is questionable and growth modulation is not possible. This case report illustrates the benefit of the team approach in correcting vertical maxillary excess along with class II skeletal deformity. A cosmetic correction was achieved by superior repositioning of maxilla with LeFort I osteotomy and augmentation genioplasty, along with orthodontic treatment. The patient's facial appearance was markedly improved along with functional and stable occlusion